Constructing Hierarchical Tectorum‐like α‐Fe2O3/PPy Nanoarrays on Carbon Cloth for Solid‐State Asymmetric Supercapacitors. Issue 4 (21st December 2016) - Wang, Libin; Yang, Huiling; Liu, Xiaoxiao; Zeng, Rui; Li, Ming; Huang, Yunhui; Hu, Xianluo
Abstract: The design of complex heterostructured electrode materials that deliver superior electrochemical performances to their individual counterparts has stimulated intensive research on configuring supercapacitors with high energy and power densities. Herein we fabricate hierarchical tectorum‐like α‐Fe2 O3 /polypyrrole (PPy) nanoarrays (T‐Fe2 O3 /PPy NAs). The 3D, and interconnected T‐Fe2 O3 /PPy NAs are successfully grown on conductive carbon cloth through an easy self‐sacrificing template and in situ vapor‐phase polymerization route under mild conditions. The electrode made of the T‐Fe2 O3 /PPy NAs exhibits a high areal capacitance of 382.4 mF cm −2 at a current density of 0.5 mA cm −2 and excellent reversibility. The solid‐state asymmetric supercapacitor consisting of T‐Fe2 O3 /PPy NAs and MnO2 electrodes achieves a high energy density of 0.22 mWh cm −3 at a power density of 165.6 mW cm −3 . Abstract : Upholstered capacitors : High energy/power densities are achieved by using hierarchically nanostructured tectorum‐like Fe2 O3 /polypyrrole (PPy; tectorum ( Tillandsia tectorum ) is a species of spikey plant) nanoarrays on conductive carbon cloth as solid‐state asymmetric supercapacitor electrodes.